Finding Italy : travel, nation and colonization in Vergil's Aeneid - Fletcher, K. F. B. (The University of Michigan Press, 2014)
The Trojans' journey to Italy in Vergil's Aeneid teaches them to love their new homeland and their new name-the Romans.